Peran Kepala Desa dalam Pemberdayaan Kelompok Budidaya Ikan “Mina Karya” di Desa Babakan, Kecamatan Pangandaran, Kabupaten Pangandaran - Rusti Oktavian; Regi Refian Garis; Asep Nurdin Rosihan Anwar (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2024)
Strengthening Village communities improves living standards, produces sustainable benefits for the community, encourages community independence and initiative, develops the Village economy, improves the environment, and forms community financial institutions, are efforts to create activities that make this possible. Increasing the creativity and productivity of the people of Babakan Village who face several obstacles in strengthening the fish cultivation population, including the dry season causing drought, this has an impact on the development of fish cultivation, the outreach and training by the Babakan Village Government for fish cultivation groups regarding their potential, the cultivator community has not been maximized. Fish lack insight and knowledge so that fish farming management is carried out by autodidacts. The conclusions obtained show that the role of the village government in strengthening the "Mina Kariya" fisheries cultivation group in Babakan Village, Pangandaran District, Pangandaran Province is basically functioning and very good. However, it still faces several obstacles, such as the lack of consensus among all breeders and it is still not optimal. So far we have not found an alternative to making our own food, so fish food still needs to be purchased. Farmers' skills and knowledge are still low and there are no alternative aquaculture techniques that can help farmers run their operations effectively. There is no research that focuses on the role of the Village Head in empowering community business groups, especially in Pangandaran Regency, so it is urgent in this research to find solutions to solve the problems that occur.